2001
DOI: 10.1007/bf03401967
|View full text |Cite
|
Sign up to set email alerts
|

Arsenite Activation of PI3K/AKT Cell Survival Pathway is Mediated by p38 in Cultured Human Keratinocytes

Abstract: analysis was performed for the determination of generation of reactive oxygen species. Results: Arsenite induced the activation of AKT at both Ser473 and Thr308, and its downstream effector eNOS in cultured human keratinocytes. Arsenite also induced phosphorylation of p38. PI-3-kinase inhibitors, Wortmannin and LY294002 inhibited arsenite-induced phosphorylation of AKT and eNOS but had no effect on phosphorylation of p38. Interestingly, however, SB203580, a known p38 inhibitor, completely inhibited arsenite-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 19 publications
0
31
0
Order By: Relevance
“…53 Increased PI3K-mediated PKB/Akt phosphorylation has been reported in β-cells exposed to high dose of arsenic. 54 The phosphorylation of PKB/Akt signaling was also one of the key steps in the activation of glucose transporter 4 (GLUT4) by insulin. 55 Thus, it has been suggested that the exposure to high dose of arsenic might mimic the action of insulin by phosphorylation of PKB/Akt-mediated GLUT4 expression in vitro.…”
Section: Arsenicmentioning
confidence: 99%
See 1 more Smart Citation
“…53 Increased PI3K-mediated PKB/Akt phosphorylation has been reported in β-cells exposed to high dose of arsenic. 54 The phosphorylation of PKB/Akt signaling was also one of the key steps in the activation of glucose transporter 4 (GLUT4) by insulin. 55 Thus, it has been suggested that the exposure to high dose of arsenic might mimic the action of insulin by phosphorylation of PKB/Akt-mediated GLUT4 expression in vitro.…”
Section: Arsenicmentioning
confidence: 99%
“…54 The phosphorylation of PKB/Akt signaling was also one of the key steps in the activation of glucose transporter 4 (GLUT4) by insulin. 55 Thus, it has been suggested that the exposure to high dose of arsenic might mimic the action of insulin by phosphorylation of PKB/Akt-mediated GLUT4 expression in vitro. However, exposure to low dose of arsenic has been shown to inhibit ISGU in 3T3-L1 adipocytes; the phosphorylation of PKB/Akt was suppressed in exposed cells, which was an important requirement for GLUT4 translocation to the cellular membrane in response to insulin.…”
Section: Arsenicmentioning
confidence: 99%
“…Increased PI-3K-mediated PKB/Akt phosphorylation has been reported in cells exposed to toxic concentrations (200-500 μM) of iAs III (McDowell et al, 1997;Souza et al, 2001). Stress-induced phosphorylation of PKB/Akt is associated with the activation of pro-survival mechanisms aimed at preventing apoptosis and promoting cell proliferation (Dudek et al, 1997;Ibuki and Goto, 2000;Zhou et al, 2000).…”
Section: Laboratory Studies Of the Effects Of As On Glucose Metabolismmentioning
confidence: 99%
“…Arsenite has been used as a chemotherapeutic drug to treat acute promyelocytic leukemia cases (44). Thus, sodium arsenite seems to trigger caspase activation by activation of AKT1 and downstream glycogen synthase 3ß (GSK3ß), which are crucial for caspase signaling network AKT1 activation they also can act as an alternate cell survival pathway that is mediated via PI-3 kinase and p38 and bypass the activation of EGF receptor in cultured human keratinocytes (45).…”
Section: Discussionmentioning
confidence: 99%